2020
DOI: 10.1021/acs.est.0c02639
|View full text |Cite|
|
Sign up to set email alerts
|

Structures of Endocrine-Disrupting Chemicals Determine Binding to and Activation of the Estrogen Receptor α and Androgen Receptor

Abstract: Endocrine-disrupting chemicals (EDCs) can interact with nuclear receptors, including estrogen receptor α (ERα) and androgen receptor (AR), to affect the normal endocrine system function, causing severe symptoms. Limited studies queried the EDC mechanisms, focusing on limited chemicals or a set of structurally similar compounds. It remained uncertain how hundreds of diverse EDCs could bind to ERα and AR and cause distinct functional consequences. Here, we employed a series of computational methodologies to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…Similarly, there are several attempts to interpret ML models to correlate factors with the chemical activity of EDCs, including unveiling features that make EDCs chemically active, determining the type of activity on the ERα or the AR, and how these features exert their functions. 45 Using ML techniques, researchers also found that the octanol−water partitioning coefficient (log K ow ) plays a dominant role in regulating plant uptake of organic contaminants, while their molecular weight plays a secondary role. 99 In recent years, data-driven analytics such as ML have become key tools for discovery in public health and ESE research to find hidden patterns and causal relationships and to identify key features, that is, chemical exposure or other social economic parameters, that are linked with health outcomes.…”
Section: Current Status Of ML Applications In Esementioning
confidence: 99%
“…Similarly, there are several attempts to interpret ML models to correlate factors with the chemical activity of EDCs, including unveiling features that make EDCs chemically active, determining the type of activity on the ERα or the AR, and how these features exert their functions. 45 Using ML techniques, researchers also found that the octanol−water partitioning coefficient (log K ow ) plays a dominant role in regulating plant uptake of organic contaminants, while their molecular weight plays a secondary role. 99 In recent years, data-driven analytics such as ML have become key tools for discovery in public health and ESE research to find hidden patterns and causal relationships and to identify key features, that is, chemical exposure or other social economic parameters, that are linked with health outcomes.…”
Section: Current Status Of ML Applications In Esementioning
confidence: 99%
“…Tertiary fragments are then used to discriminate agonists, antagonists, or mixed agonist and antagonist modes of action. 27 Models for RARs and VDR are characterised by a lower sensitivity. A detailed documentation of each workflow and the associated fragments is available on the VEGAHUB website.…”
Section: Vega Nrmeamentioning
confidence: 99%
“…Computational methods could be used to evaluate and screen chemicals on their potential endocrine activity, which is significant in minimizing the adverse impacts of EDCs on human health and the environment and finally realizing the sustainable assessment and management of EDCs. To date, extensive predictive models were available for the end points related to disruption effects of nuclear receptors. Even some models for predicting the disruption effects of nuclear receptors have been integrated into several pieces of publicly available software, e.g., VAGE () and OECD QSAR Toolbox (). However, the predictive models for the binding potency of compounds with nonreceptor mediated targets, e.g., hormone transporters, were much less than that of nuclear receptors .…”
Section: Introductionmentioning
confidence: 99%